2015
DOI: 10.3892/ol.2015.3140
|View full text |Cite
|
Sign up to set email alerts
|

Genomic losses at 5q13.2 and 8p23.1 in dysplastic hepatocytes are common events in hepatitis B virus-related hepatocellular carcinoma

Abstract: Abstract. Chromosomal loci with genomic imbalances are frequently identified in hepatocellular carcinoma (HCC). Greater than two-thirds of hepatitis B virus (HBV)-relatedHCCs originate from liver cirrhosis following a duration of up to two decades. However, it is unclear whether these genomic imbalances occur and accumulate in dysplastic hepatocytes of the cirrhotic liver during the progression from regenerated nodules to preneoplastic lesions, including dysplastic nodules (DN). In the present study, high-grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…We did not find any significant difference when comparing recurrently mutated genes between 52 cirrhotic and 63 non-cirrhotic samples for which cirrhotic status was available using CAP1. The LOH events [10,4952] and CNVs [9–11,52,53] observed within our cohort are similar to those previously observed in cirrhotic HCC using alternative, investigative approaches including SNP array analysis. Within these regions, several genes such as LAMA2, ATK3, EFF1A1 , and PFN1 [14,5456] have been previously investigated in the context of HCC development and progression.…”
Section: Discussionsupporting
confidence: 83%
“…We did not find any significant difference when comparing recurrently mutated genes between 52 cirrhotic and 63 non-cirrhotic samples for which cirrhotic status was available using CAP1. The LOH events [10,4952] and CNVs [9–11,52,53] observed within our cohort are similar to those previously observed in cirrhotic HCC using alternative, investigative approaches including SNP array analysis. Within these regions, several genes such as LAMA2, ATK3, EFF1A1 , and PFN1 [14,5456] have been previously investigated in the context of HCC development and progression.…”
Section: Discussionsupporting
confidence: 83%
“…We did not find any significant difference when comparing recurrently mutated genes between 52 cirrhotic and 63 non-cirrhotic samples for which cirrhotic status was available using CAP1. The LOH events [10,[49][50][51][52] and CNVs [9][10][11]52,53] observed within our cohort are similar to those previously observed in cirrhotic HCC using alternative, investigative approaches including SNP array analysis. Within these regions, several genes such as LAMA2, ATK3, EFF1A1, and PFN1 [14,[54][55][56] have been previously investigated in the context of HCC development and progression.…”
Section: Genomic Landscape Of Non-cirrhotic Hcc Largely Resembles Tha...supporting
confidence: 81%
“…General transcription factor IIH subunit (GTF2H) is located on 5q13.2 and encodes the 44-kDa RNA polymerase II TFIIH protein subunit 2 that interacts with other TFIIH subunits in the nucleotide excision repair pathway. Zhao et al (48) identified 30 (36.1%) of 83 HCC cases with loss of heterogeneity at 5q13.2, in which the tumor-associated gene GTF2H2 was present. GTF2H2 is an estrogen signaling pathway gene in breast cancer and is downregulated by luteolin (51).…”
Section: Estrogen May Serve An Inhibitory Role In Sex Disparity In Hcmentioning
confidence: 99%